Multiperspective and Multimethod Evaluation of Flexible and Integrative Psychiatric Care Models in Germany: Study Protocol of a Prospective, Controlled Multicenter Observational Study (PsychCare) - Soltmann, Bettina; Neumann, Anne; March, Stefanie; Weinhold, Ines; Häckl, Dennis; Kliemt, Roman; Baum, Fabian; Romanos, Marcel; Schwarz, Julian; von Peter, Sebastian; Ignatyev, Yuriy; Arnold, Katrin; et al. (Frontiers in Psychiatry, 2021)
Background New cross-sectoral mental health care models have been initiated in Germany to overcome the fragmentation of the German health care system. Starting in 2013, flexible and integrative psychiatric care model projects according to §64b SGB V German Social Law (FIT64b) have been implemented. “PsychCare” combines quantitative and qualitative primary data with routine health insurance data for the evaluation of these models. Effects, costs and cost-effectiveness from the perspectives of patients, relatives and care providers are compared with standard care. Additionally, quality indicators for a modern, flexible and integrated care are developed. This article describes the rationale, design and methods of the project. Methods “PsychCare” is built on a multiperspective and multimethod design. A controlled prospective multicenter cohort study is conducted with three data collection points (baseline assessment, follow-up after 9 and 15 months). A total of 18 hospitals (10 FIT64b model and 8 matched control hospitals) have consecutively recruited in- and outpatients with pre-specified common and/or severe psychiatric disorders. Primary endpoints are differences in change of health-related quality of life and treatment satisfaction. Sociodemographic and service receipt data of the primary data collection are linked with routine health insurance data. A cost-effectiveness analysis, a mixed method, participatory process evaluation by means of qualitative surveys and the development of quality indicators are further elements of “PsychCare”. Discussion and practical implications The results based on data from different methodological approaches will provide essential conclusions for the improvement of hospital based mental health care in Germany. This should result in the identification of key FIT64b elements that can be efficiently implemented into standard care in Germany and re-structure the care strongly aligned to patient needs.